THE CONNECTION BETWEEN COMPETITIVENESS AND SUSTAINABILITY IN TOURISM DESTINATIONS: EXAMINING THE HARD, SOFT, AND MODERATING EFFECTS OF KNOWLEDGE SHARING - Chin, Chee Hua; Lo, May Chiun; Wong, Winnie Poh Ming (Universidad de Huelva Publication, 2022)
This paper aims to assess the impact of hard and soft measures on the competitiveness of tourism destinations. Additionally, this article examines the impact of tourism destination competitiveness on rural tourism sustainability management. Following that, knowledge sharing is used as a moderator variable to demonstrate its moderating effect on the relationship between tourism destination competitiveness and rural tourism sustainability. A total of 390 respondents, including both domestic and international tourists, who visited the six rural tourism destinations in Sarawak, Malaysia, voluntarily participated in this study. A PLS-SEM approach was used to evaluate the developed model, and WarpPLS software was used to perform the PLS estimate and hypotheses testing. The empirical findings indicated that destination appeal, tourism infrastructure, and service quality all have a significant and positive effect on the competitiveness of tourism destinations. Additionally, it was discovered that tourism destination competitiveness has a positive and significant effect on the sustainable management of rural tourism destinations.